Investigating the determinants of E-banking loyalty for large business customers: two empirical models - Fragata, A. (2017)
The current research paper proposes two models for the determinants of E-banking Loyalty for large business customers. The results demonstrated that five main quality dimensions were identified for the e-banking portals: assurance, reliability, convenience and quality monitoring by the financial director of the company. The results also confirm that e-banking quality has a strong impact on e-banking loyalty via the mediating effect of e-trust and switching costs have strong a impact on e-banking loyalty. Further our findings also suggest that interpersonal relationships generated between the bank manager and the decision maker of the company have a strong impact on the perceptions of service quality in online banking, and will also affect positively E-Banking Loyalty. Banking, e-loyalty, e-banking quality.